Experimental and numerical validation of the modal analysis of a cantilever beam using LabVIEW and finite element simulation (Ciencias de la Ingeniería y Aplicadas, 2025)
This study presents a cross-validation between experimental modal analysis (EMA) and numerical simulation using the finite element method (FEM) on a cantilever beam. The physical testing involved a National Instruments CompactDAQ system and LabVIEW software, with impact excitation using an instrumented hammer and signal acquisition through piezoelectric accelerometers. The numerical model was built in SolidWorks and simulated using Autodesk Inventor Nastran and LISA. The comparison of natural frequencies revealed strong agreement between both approaches, with relative errors below 12% across the first five modes. The validated procedure, tested on a simple structure, demonstrates potential for extension to the dynamic analysis of more complex systems, such as mechanical components, buildings, or bridges.This approach offers a feasible and cost-effective alternative for structural validation in academic, industrial, and diagnostic applications
Keywords: experimental modal analysis; finite element method; numerical-experimental correlation; mechanical structures; structural validation; LabVIEW